Priority needs assessment for digital citizenship competency development of secondary school administrators under provincial administrative organizations in Northeastern Thailand - Surasa, Pruchya; Prasertcharoensuk, Thanomwan; Kanjug, Parnpitcha (Edelweiss Applied Science and Technology, 2026)
This research examines the components of digital citizenship competency and evaluates the priority development needs among secondary school administrators within Provincial Administrative Organizations in Northeastern Thailand. Using a quantitative survey design, data were gathered from a stratified random sample of 582 educational personnel. The instrument assessed current and ideal states across five key domains: Digital Ethics, Communication, Literacy, Security, and Participation. Data analysis involved calculating means, standard deviations, and the Modified Priority Needs Index (PNI). Results indicated that the overall current competency level was moderate (3.36), while the desired level was at the highest (4.60). Notably, Digital Literacy was identified as the most urgent area for development (PNI = 0.44), followed by Digital Security and Digital Ethics. Conversely, Digital Communication and Participation showed lower priority indices. These findings highlight a significant gap in technical and normative skills compared to interaction skills. Therefore, strategic policies should focus on improving digital literacy, security, and ethical foundations to better empower educational administrators amid ongoing digital challenges.